Family Financial Literacy as a Life Skill for Divorce Prevention in Central Kalimantan Province - Yogi Yogi; Khairil Anwar; Mowafg Abrahem Masuwd (Yayasan Rahmat Islamiyah, 2026)
Financial management is all activities related to how to obtain, use and manage funds to achieve overall family goals. Family financial management has four indicators, namely the obligation to pay debts, basic needs, desires/social and charity. The purpose of this study is to find out how Family Financial Literacy as a Life Skill Prevents Divorce in Central Kalimantan Province. This study uses a library research method with a qualitative-descriptive approach. The author can dig up the information data needed in this writing through interviews and observations that examine the provisions of family financial literacy as a life skill to prevent divorce. The results of this study (1) that earning a living is the husband's obligation, but if the wife wants to work and earn a living together, this is highly recommended because the income of the husband and wife who work will be more optimal and can help cover household needs, so that if household needs are met properly, it will reduce conflict in the household and indirectly will reduce the divorce rate in Central Kalimantan Province. (2) A harmonious atmosphere at home helps create balance in daily life, allowing family members to focus more on other aspects of life such as career, education, and hobbies. Happy moments and family togetherness create lifelong memories, building a strong foundation for lasting family relationships. Harmony within the household can prevent conflict and divorce in Central Kalimantan Province, resulting in a significant drop in the divorce rate.